Access to Medicines, Access to Markets - Sismondo, Sergio (Frontiers in Sociology, 2020)
This article explores some uses by the pharmaceutical industry of language from the “access to medicines” movement in global health, sometimes for goals almost completely opposite to those of the movement. Important in the context of extremely expensive treatments, the industry draws on the idealistic discourse around access to medicines to create a very specific continuity between the needs of the Global South and its own marketing needs. By focusing on “access”, the industry can promote the opening up of markets in relatively wealthy countries with important public or highly regulated payers.